L’importance internationale du développement économique dans les régions arctiques - Critchley, W. (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1989)
The economic development of the northern regions of the USSR, United States, Canada, Norway and Denmark (Greenland) is examined with reference to the possible sources and timing of development in each state. The conclusion is that economic development for these Arctic littoral states is extraordinarily dependent upon the development of non-renewable natural resources - especially petroleum hydrocarbons — and, to a lesser extent, certain renewable resources. In addition, current world prices for the relevant resources are sufficiently low that development activity in each state ranges from moderate to modest: as long as prices remain at these levels, the current timing and pace of development is not likely to increase. A complex mix of factors is involved in estimating the international importance of such economic development, but the current moderate or modest levels of development activity provide a « breathing space » for interstate relations among the Arctic littoral states. This is the opportunity to explore and develop cooperative institutions and mechanisms for further economic development in the face of pressures that might otherwise promote conflict.